Analysis of Knowledge Management System in The Book of Fiqih Mobile Application Bulughul Islamic Law Based on Usability - T, Thoyyibah; Haryono, Wasis; Puspitasari, Tita; Megasari, Dian (The Pontianak State Institute of Islamic Studies, 2019)
Mobile applications have become a good learning tool. This application involves technology that can be accessed anytime and anywhere. But keep in mind also the progress of science and technology can not be separated from the development, discovery and progress of science in the heyday of Muslims. Islam is very influential in the world and even a great deal of learning is applied to certain methods. The aim of this study was to analyze the mobile learning of the Book of Fiqih in the Islamic Law of the Bulughul Haram by mapping knowledge and evaluation of SUMI (the Usability Measurement Inventory). This study uses a method adopted from KMSLC (Knowledge Management System Life Cycle). The results of this study are mapping knowledge and measuring the quality of a system